GENERASI Z DALAM KHAZANAH MODERASI BERAGAMA DI INDONESIA - Selamet Afrian, Selamet Afrian; Saumantri, Theguh (SETYAKI : Jurnal Studi Keagamaan Islam, 2024)
Abstract: Generation Z, who grew up in the era of digital technology and is connected globally, has an increasingly important role in strengthening the treasures of religious moderation in Indonesia. This article aims to investigate the special role of Generation Z in the context of religious moderation, as well as its impact on inter-religious harmony in Indonesia. Through a literature review and empirical data analysis, this article reveals the contribution of Generation Z in promoting attitudes of tolerance, interfaith cooperation and open dialogue in Indonesian society. Keywords: Generation Z, Characteristics, Religious Moderation